Current research in Egyptology 2017 : proceedings of the Eighteenth Annual Symposium: University of Naples, "L'orientale" 3-6 May 2017 - Incordino, Ilaria,; Barocas, Claudio, (Archaeopress Publishing Ltd, 2018)
'Current Research in Egyptology 2017' presents papers delivered during the eighteenth meeting of this international conference, held at the University of Naples 'L'Orientale', 3-6 May, 2017. Some 122 scholars from all over the world gathered in Naples to attend three simultaneous sessions of papers and posters, focused on a large variety of subjects: Graeco-Roman and Byzantine Egypt, Nubian Studies, Language and Texts, Art and Architecture, Religion and Cult, Field Projects, Museums and Archives, Material Culture, Mummies and Coffins, Society, Technologies applied to Egyptology, Environment.